A configuration-based approach to integrating dynamic capabilities and market transformation in small and medium-sized enterprises to achieve firm performance. (May 2015) - Rice, John; Liao, Tung-Shan; Galvin, Peter; Martin, Nigel
This article develops and tests a model integrating dynamic organisational capabilities, market transformation arrangements and firm performance. This model addresses weaknesses in previous empirical research by integrating accumulation and path dependency in measures of dynamic capabilities. Using a sample of 444 small and medium-sized Australian manufacturing firms, the study finds that performance is driven by the successful deployment of dynamic capabilities; such performance is mediated by purposeful market transformation strategies.